Factors associated with psychoactive substance use among professional truck drivers - Ângela Maria Mendes Abreu; Rafaela Maria Figueiredo da Costa; Rafael Tavares Jomar; Luciana Fernandes Portela (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to identify factors associated with the use of psychoactive substances among professional truck drivers. Methods: cross-sectional study that investigated the use of at least one psychoactive substance and its association with sociodemographic, occupational, and health characteristics in 354 professional truck drivers. Researchers collected data through face-to-face interviews using forms. Multiple regression analyzes estimated prevalence ratios (PR) and respective 95% confidence intervals (95%CI). Results: lower family income (PR: 2.03; 95%CI: 1.08-3.83), symptoms of insomnia (PR: 2.18, 95%CI: 1.46-3.26), and long working hours (PR: 1.95, 95%CI: 1.30-2.92) independently associated with the use of at least one psychoactive substance. Conclusions: a set of sociodemographic, occupational, and health variables acts at distinct levels and is independently associated with the use of psychoactive substances among professional truck drivers.